Heterogeneity of beliefs and information rigidity in the crude oil market: Evidence from survey data - Robert Czudaj (Chemnitz University of Technology, Faculty of Economics and Business Administration, 2021)
This paper assesses information contained in the micro dataset of the ECB Survey of Professional Forecasters regarding quarterly Brent crude oil price forecasts. We examine the expectations building mechanism by referring to the processing of information and confirm the presence of information rigidity within the crude oil market. However, our findings also show that simple models of imperfect information considered in the literature are insufficient to explain the behavior of professional forecasters. We provide additional stylized facts which are helpful for designing more elaborate imperfect information models.
Keywords: D83; D84; E44; 330; Crude oil; Disagreement; Expectations; Heterogeneity; Information rigidity; Survey data